1988
DOI: 10.1002/ana.410230106
|View full text |Cite
|
Sign up to set email alerts
|

Familial alzheimer's disease in american descendants of the volga germans: Probable genetic founder effect

Abstract: Five families are described in which autopsy-confirmed presenile Alzheimer's disease (AD) has occurred in men and women over multiple generations consistent with autosomal dominant inheritance. All 5 families are descendants of a group of immigrants known as the Volga Germans who came to the United States between 1870 and 1920. Their ancestors moved from Germany to the southern Volga region of Russia in the 1760s. All 5 American families are descendants of persons originally living in two small adjacent Volga … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(58 citation statements)
references
References 11 publications
1
57
0
Order By: Relevance
“…Evidence for an additional early-onset locus comes from studies of the VG kindreds. These families come from a group of Germans who, in the 1760s, emigrated to the Volga river region of Russia (80,91 Linkage analysis of the VG families with chromosome 21 markers has yielded negative results (23,24,29) and no mutations have been identified in theAPP gene (29). Similarly, linkage analysis with chromosome 14 markers nearAD3 (63,71) and with the chromosome 19 APOCII STRP locus gave negative results (68,92).…”
Section: The Vg Kindredsmentioning
confidence: 99%
“…Evidence for an additional early-onset locus comes from studies of the VG kindreds. These families come from a group of Germans who, in the 1760s, emigrated to the Volga river region of Russia (80,91 Linkage analysis of the VG families with chromosome 21 markers has yielded negative results (23,24,29) and no mutations have been identified in theAPP gene (29). Similarly, linkage analysis with chromosome 14 markers nearAD3 (63,71) and with the chromosome 19 APOCII STRP locus gave negative results (68,92).…”
Section: The Vg Kindredsmentioning
confidence: 99%
“…Additional pedigree data were collected from 3 international studies: the Dominantly Inherited Alzheimer Network (DIAN) Study, 9 a large Colombian kindred carrying the PSEN1 E280A mutation, 14 and a set of 11 extended families of Volga German ancestry carrying an identical PSEN2 N141I mutation due to a genetic founder effect. 5,15 Updated findings from a previously published multigenerational PSEN1 L286V kindred were provided by the investigator. 16 To avoid potential double reporting, pedigrees for each mutation type were manually examined for possible duplicates, and these were removed where identified.…”
mentioning
confidence: 99%
“…Familial forms of this disor der have been repeatedly demonstrated in large pedigrees of families with multiple affected members [2][3][4][5][6][7][8] and family history studies have shown increased risk of de mentia to relatives of AD probands in comparison to AD probands. This represents the first report of morbid risk estimates based on a sample with prospective clinical as well as neuropathologic diagnoses.…”
Section: Introductionmentioning
confidence: 99%